MODEL STATIS DAN DINAMIS DAMPAK INFLASI GLOBAL TERHADAP MAKROEKONOMI INDONESIA - Soelistyo, Aris (Faculty of Economics and Business, University of Muhammadiyah Malang, 2012)
The aim of this research is to analyse the effect of global inflation to macroeconomic in Indonesia. ARCH model used to analyse the influence of global inflation to macroenomic. According to the result analysis reveals that; first, based on the ARCH approach and market equilibrium global inflation have negative influence to GDP. Second, based on the goods and money market equilibrium, global inflation has positive influence to GDP. Third, global inflation in static inflation models has siginificant influence to domestic inflation. It’s little bit small than in dinamic inflation models. Fourth, ecxhange currency rate has positive significant influnced to export magnitude